Penyusutan Kalium Iodat dalam Garam Beryodium Selama Penyimpanan Suhu Rendah: Reduction of Potassium Iodat in Iodized Salt at low Temperature - Bahja Bahja; Wery Aslinda; Abnon Yesria (Svasta Harena: Jurnal Ilmiah Gizi, 2021)
The contribution of iodine from food is thought to depend largely on the consumption of iodized salt. Potassium iodate (KIO3) is often used as a source of iodine in iodized salt, but experimental data on the stability of potassium iodate at low temperature storage are still very limited. This study aims to determine the effect of KIO3 conditions of iodized salt stored at low temperatures (0oC, 5oC, 13oC, 15oC, and a temperature range of 29-33oC). This research is a descriptive type, which aims to determine the KIO3 content of iodized salt at low temperature storage using salt samples purchased from modern markets. The results obtained indicate that the storage at low temperatures of iodized salt resulted in a decrease in KIO3 levels. The loss of KIO3 in iodized salt tends to increase the lower the temperature. Depreciation of KIO3 content in iodized salt at low temperature storage, namely: 0oC (17.4%), 5oC (7.3%), 13oC (6.8%), 15oC (2.4%) and a temperature range of 29-33oC ( 2.3%). Based on the results of the study, it can be concluded that the KIO3 content in iodized salt can experience shrinkage at low temperature storage.